A marine microbial mineralized coating and preparation method thereof

Through the preparation method of marine microbial mineralized coating, the dense carbonate layer is formed by using Syvarella sporiasis and L-aspartate, which solves the problems of high cost, pollution and construction difficulty of existing marine corrosion protection technologies, and achieves efficient anti-corrosion performance improvement.

CN119553273BActive Publication Date: 2025-04-08UNIV OF SCI & TECH BEIJING +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510112624.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-08
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

The existing marine corrosion prevention technology has problems such as high cost, pollution release and construction difficulty, and the shielding effect of microbial mineralized coatings fails in complex environments.

Method used

Using the preparation method of marine microbial mineralized coating, the target metal material is sterile and immersed in the culture medium of Symptoms for the first culture, and then added L-aspartate to form a biomineralized nucleation solution, and the second culture is carried out to form a dense, flat microbial mineralized coating.

Benefits of technology

A denser, flatter and stable microbial mineralized coating is formed, which significantly improves corrosion resistance and can effectively deal with complex marine environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553273B_ABST
    Figure CN119553273B_ABST
Patent Text Reader

Abstract

The present application provides a marine microbial mineralized coating and a preparation method thereof, and relates to the field of marine anti-corrosion coatings. The preparation method of the marine microbial mineralized coating comprises: after aseptically treating the target metal material, immersing it in a culture solution of Shewanella putrefaciens for a first culture to obtain a metal material with a biofilm; adding L-calcium aspartate to the culture solution of Shewanella putrefaciens to obtain a biomineralization nucleation solution, and performing a second culture to obtain a metal material with the marine microbial mineralized coating. The method provided in the present application regulates the carbonate layer induced by Shewanella putrefaciens by accessing an inorganic calcium source L-calcium aspartate. The morphology of the microbial mineralized coating mediated and regulated by L-calcium aspartate changes from a general calcite crystal form to a slate-like form, forming a more dense, smooth and stable microbial mineralized coating with excellent anti-corrosion properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of marine anti-corrosion coatings, and in particular to a marine microbial mineralization coating and a preparation method thereof. Background Art

[0002] The marine environment is complex and changeable, and the harsh natural conditions cause marine engineering metal materials to be corroded to varying degrees and fail. Marine corrosion not only causes safety problems but also brings economic losses, and is one of the threats faced in the development and utilization of marine resources.

[0003] Microbiologically influenced corrosion inhibition (MICI) has attracted extensive attention in the field of corrosion and protection as a new potential industrial anti-corrosion method. At present, most traditional anti-corrosion methods rely on chemical or electrochemical means, which often face a series of problems such as high cost, release of pollutants, and difficulty in construction. The toxic and harmful substances produced during use are complex in composition and are inevitably released into the air, soil and water sources, causing irreversible damage to the environment.

[0004] Microbial mineralization is one of the main means of MICI. Microbial mineralization refers to the process of inorganic mineral formation participated and regulated by microorganisms, their metabolites, organic matter, etc. There are two main forms of microbial mineralization, one is microbial controlled mineralization, and the other is microbial induced mineralization. After microorganisms attach to the metal surface to form a biofilm, the occurrence of the induced mineralization process will provide a certain degree of protection for the metal matrix. Different types of bacteria will form minerals of different compositions in a specific environment, such as phosphates, carbonates, and iron-containing minerals, which can effectively inhibit the corrosion of metal materials. In recent years, microbial mineralization technology has been widely used in biocement, slope reinforcement and sand control, concrete crack repair, and microbial in-situ mineralization repair to reduce heavy metal pollution. However, the mineralized layer formed by microbial mineralization technology often forms an uneven mineralized layer due to the abnormal biofilm, which seriously affects the shielding effect of the mineralized layer and loses its protective performance when facing a complex environment. Summary of the invention

[0005] The purpose of this application is to provide a marine microbial mineralization coating and a preparation method thereof to solve the above-mentioned problems.

[0006] To achieve the above objectives, this application adopts the following technical solutions:

[0007] A method for preparing a marine microbial mineralized coating, comprising:

[0008] After the target metal material is aseptically treated, it is immersed in a culture solution of Shewanella putrefaciens for a first culture to obtain the metal material with a biofilm;

[0009] Calcium L-aspartate is added to the culture solution of the Shewanella putrefaciens to obtain a biomineralization nucleation solution, and a second culture is performed to obtain a metal material with the marine microbial mineralization coating.

[0010] Preferably, the method for preparing the culture solution of Shewanella putrefaciens comprises:

[0011] The putrefactive Shewanella is inoculated into a marine liquid culture medium for a third culture to obtain the putrefactive Shewanella culture solution.

[0012] Preferably, the marine liquid culture medium comprises:

[0013] Peptone 4.9-5.1 g / L, yeast extract 0.9-1.1 g / L, ferric citrate 0.09-0.11 g / L, NaCl 19.35-19.55 g / L, MgCl 2 5.95-6.01 g / L, Na 2 SO 4 3.2-3.28 g / L, KCl 0.52-0.58 g / L, Na 2 CO 3 0.13-0.19 g / L, KBr 0.05-0.11 g / L, SrCl 2 0.031-0.037 g / L, SrBr 2 0.05-0.11 g / L, H 3 BO 3 0.019-0.025 g / L, NaSiO 3 0.003-0.005 g / L, NaF 0.0021-0.0027 g / L, NH 4 NO 3 0.0013-0.0019 g / L, NaH 2 PO 4 0.005-0.011 g / L.

[0014] Preferably, the temperature of the third culture is 30-33°C, the stirring speed is 180-220rpm / min, and the time is 14-18h;

[0015] The ratio of the inoculation volume of the putrefactive Shewanella to the volume of the marine liquid culture medium is 1-2:100, and the concentration of the putrefactive Shewanella before inoculation is 1×10 7 -1×10 8 CFU / mL.

[0016] Preferably, the first culture is carried out at a temperature of 30-33°C for 14-18 hours;

[0017] The temperature of the second culture is 30-33° C., the time is 1-14 days, and the second culture is static culture.

[0018] Preferably, the concentration of calcium L-aspartate in the biomineralization nucleation solution is 2.74-2.8 g / L.

[0019] Preferably, the calcium L-aspartate is sterilized before use and then filtered at room temperature using a 0.22 μm sterile microporous filter membrane.

[0020] The present application also provides a marine microbial mineralized coating, which is prepared using the preparation method of the marine microbial mineralized coating.

[0021] Preferably, the marine microbial mineralized coating has an undulation degree of 3-3.4 μm.

[0022] Preferably, the thickness of the marine microbial mineralized coating is 12-15 μm.

[0023] Compared with the prior art, the beneficial effects of this application include:

[0024] The preparation method of the marine microbial mineralized coating provided by the present application regulates the carbonate layer induced by Shewanella putrefaciens by accessing an inorganic calcium source, calcium L-aspartate. The morphology of the microbial mineralized coating mediated and regulated by calcium L-aspartate changes from a general calcite crystal form to a slate-like shape. By additionally introducing a large amount of aspartic acid roots, as a nitrogen-containing substrate, the transamination and deamination of Shewanella putrefaciens are enhanced to produce free ammonia gas, providing a good environment for the carboxyl and amino groups of calcium L-aspartate to be adsorbed on the surface of the metal sample to form an adsorption film. In this environment, aspartic acid roots selectively attach to the high-energy crystal faces of calcium carbonate grains, regulate their growth, and form a microsphere morphology, thereby forming a more dense, smooth and stable microbial mineralized coating with excellent anti-corrosion properties. In addition, the biomineralized coating provided by the present application is prepared with marine microorganisms as the core, so it can effectively cope with complex marine environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0026] Figure 1The macroscopic morphology of the Q235 steel sheet sample coated with the biomineralization coating in Example 1 of the present application and the Q235 steel sheet sample in Comparative Example 1;

[0027] Figure 2 The microscopic SEM images of the Q235 steel sheet sample coated with the biomineralization coating in Example 1 of the present application and the Q235 steel sheet sample in Comparative Example 1;

[0028] Figure 3 The EDS element analysis diagram of the Q235 steel sheet sample coated with the biomineralization coating in Example 1 of the present application and the Q235 steel sheet sample in Comparative Example 1;

[0029] Figure 4 The cross-sectional SEM image and element distribution diagram of the Q235 steel sheet sample coated with the biomineralization coating in Example 1 of the present application;

[0030] Figure 5 XRD composition diagrams of the Q235 steel sheet sample coated with the biomineralization coating in Example 1 of the present application and the Q235 steel sheet samples in Comparative Example 1, Comparative Example 3, and Comparative Example 4;

[0031] Figure 6 The electrochemical impedance diagram and Bode diagram of the Q235 steel sheet sample coated with the biomineralization coating in Example 1 of the present application and the Q235 steel sheet sample in Comparative Example 1;

[0032] Figure 7 Potentiodynamic polarization diagrams of the Q235 steel sheet sample coated with the biomineralization coating in Example 1 of the present application and the Q235 steel sheet sample in Comparative Example 1;

[0033] Figure 8 The macroscopic morphology of the Q235 steel sheet sample coated with the biomineralization coating and the corresponding Q235 steel sheet sample of the sterile control group of the comparative example 3 of the present application;

[0034] Fig. 9 The microscopic SEM images of the Q235 steel sheet sample coated with the biomineralization coating and the corresponding Q235 steel sheet sample of the sterile control group of the comparative example 3 of the present application are shown;

[0035] Fig.10 This is an EDS element analysis diagram of a Q235 steel sheet sample coated with a biomineralization coating and a corresponding Q235 steel sheet sample of a sterile control group in Comparative Example 3 of the present application;

[0036] Fig.11 The cross-sectional SEM image and element distribution diagram of the Q235 steel sheet sample coated with the biomineralization coating in Comparative Example 3 of the present application;

[0037] Fig.12The electrochemical impedance diagram and Bode diagram of the Q235 steel sheet sample coated with the biomineralization coating and the corresponding Q235 steel sheet sample of the sterile control group of the comparative example 3 of the present application;

[0038] Fig.13 Potentiodynamic polarization diagrams of the Q235 steel sheet sample coated with the biomineralization coating and the corresponding Q235 steel sheet sample of the sterile control group in comparative example 3 of the present application;

[0039] Fig.14 The macroscopic morphology of the Q235 steel sheet sample coated with the biomineralization coating in Comparative Example 4 of the present application and the corresponding Q235 steel sheet sample in the sterile control group;

[0040] Fig.15 The microscopic SEM images of the Q235 steel sheet sample coated with the biomineralization coating in Comparative Example 4 of the present application and the corresponding Q235 steel sheet sample in the sterile control group;

[0041] Fig.16 This is an EDS element analysis diagram of a Q235 steel sheet sample coated with a biomineralization coating in Comparative Example 4 of the present application and a corresponding Q235 steel sheet sample in a sterile control group;

[0042] Fig.17 The cross-sectional SEM image and element distribution diagram of the Q235 steel sheet sample coated with the biomineralization coating in Comparative Example 4 of the present application;

[0043] Fig.18 The electrochemical impedance diagram and Bode diagram of the Q235 steel sheet sample coated with the biomineralization coating in Comparative Example 4 of the present application and the corresponding Q235 steel sheet sample of the sterile control group;

[0044] Fig.19 The potentiodynamic polarization diagrams of the Q235 steel sheet sample coated with the biomineralization coating in Comparative Example 4 of the present application and the corresponding Q235 steel sheet sample in the sterile control group. DETAILED DESCRIPTION

[0045] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0046] Example 1

[0047] This embodiment (hereinafter referred to as a biomineralization coating group) provides a marine microbial mineralization coating, and the preparation method thereof is as follows:

[0048] (1) Bacterial culture:

[0049] The marine bacteria-Shewanella putrefaciens was inoculated into the sterilized liquid culture medium at a volume percentage of 1%, and cultured at 30°C and 200 rpm / min for 18 hours. The bacterial culture solution was obtained by mixing at a volume ratio of 1:100.

[0050] Liquid culture medium (marine liquid culture medium) includes: peptone 5.0 g / L, yeast extract powder 1.0 g / L, ferric citrate 0.1 g / L, NaCl 19.45 g / L, MgCl 2 5.98 g / L, Na 2 SO 4 3.24 g / L, KCl 0.55 g / L, Na 2 CO 3 0.16 g / L, KBr 0.08 g / L, SrCl 2 0.034 g / L, SrBr 2 0.08 g / L, H 3 BO 3 0.022 g / L, NaSiO 3 0.004 g / L, NaF 0.0024 g / L, NH 4 NO 3 0.0016 g / L, NaH 2 PO 4 0.008 g / L.

[0051] (2) Biofilm growth:

[0052] The Q235 steel sheet was polished with 240 mesh, 400 mesh, 600 mesh, 800 mesh, and 1000 mesh silicon carbide sandpaper until the surface scratches were consistent, then cleaned with anhydrous ethanol in an ultrasonic bath and dried with N2. The treated Q235 steel was placed on a clean bench, sprayed with 75% alcohol, and irradiated with ultraviolet light for 30 minutes. It was then placed in a bacterial culture solution and cultured at 30°C for 18 hours to obtain a Q235 steel sheet with a biofilm.

[0053] (3) Calcium carbonate deposition

[0054] The L-aspartate calcium powder with a corresponding concentration of 2.77 g / L was placed on a clean bench and irradiated with ultraviolet light for 30 minutes. Then, the bacterial culture solution was added through a 0.22 μm microfiltration membrane to obtain a purified biomineralization nucleation solution. The Q235 steel sheet with the biofilm was placed in the purified biomineralization nucleation solution and cultured at 30°C for 1-14 days to obtain a Q235 steel sheet with a biomineralization coating.

[0055] Comparative Example 1

[0056] Different from Example 1, no Shewanella putrefaciens was inoculated (hereinafter and in the figures referred to as the control group).

[0057] Figure 1 , Figure 2 The macroscopic morphology and SEM images of the Q235 steel sheet with and without biomineralization coating are shown respectively. Figure 1 As shown, compared with the control group, the surface of the Q235 steel sheet in the biomineralization coating group was covered with a uniform and flat dark gray product layer of about 14 μm, and the metallic luster was obviously lost compared with the sterile group, and no signs of corrosion were found. Figure 2 As shown, SEM observation revealed that the surface of the sample had a slate-like morphology with fine cracks distributed on the surface. Under the regulation of L-aspartate calcium as a calcium source, Shewanella putrefaciens could induce the formation of a relatively dense biomineralized coating on the surface of the Q235 steel sheet sample.

[0058] Figure 3 The EDS composition analysis results of the biomineralized coating are shown. Figure 3 As shown in the figure, after testing its composition, it was found that the main components of its surface products are C, O and Ca. This shows that under the regulation of calcium L-aspartate as a calcium source, Shewanella putrefaciens can induce the formation of a relatively dense CaCO on the surface of the Q235 steel sheet sample. 3 Sedimentary layer.

[0059] Figure 4 The cross-sectional morphology observation and EDS component analysis results of the biomineralized coating are shown. Figure 4 As shown, the morphology of the biomineralized coating under the regulation of L-aspartic acid calcium is relatively dense as a whole, the surface undulation of the biomineralized coating is small, the difference between the maximum and minimum thickness is only 3.4μm, and there is no enrichment of Cl element, showing tolerance and resistance to chloride ions in the marine environment.

[0060] Figure 5 The XRD results of biomineralized coatings mediated by calcium L-aspartate are shown. Figure 5 As shown in the figure, in the control group, signal peaks were detected at 44.7˚, 65.1˚, and 82.4˚ on the surface of the Q235 steel sample. Combined with the SEM morphology and EDS composition results, since the corrosion product layer on the surface of the Q235 steel sample in the control group was thin, only the characteristic peak of elemental iron was detected by XRD. In the biomineralization coating group, the diffraction peaks mediated by calcium L-aspartate showed that the mineralization layer on the surface of the Q235 steel sample was composed of CaCO 3 , and the diffraction peak positions are 29.5˚, 37˚ and 47.9˚ respectively.

[0061] Figure 6 , Figure 7 The anti-corrosion performance test results of Q235 steel sheets with biomineralized coatings are shown. Figure 6 (a, b) are the electrochemical impedance and Bode diagrams of Q235 steel samples in the control group. Figure 6 (c, d) are the electrochemical impedance and Bode diagrams of the Q235 steel sample in the biomineralization coating group. The low-frequency impedance modulus of the Q235 steel sample in the biomineralization coating group is higher than that in the control group, and increases with the increase of culture time, reaching 5.02×10 4 Ω•cm 2 , which is 1.7 times the low-frequency impedance modulus value of the control group. Figure 7 The potentiodynamic polarization curves of Q235 carbon steel samples mediated by L-aspartate calcium in the control group and biomineralized coating group are shown in Figure 2. Compared with the control group, the polarization curve mediated by L-aspartate calcium showed an obvious overall left shift, the anodic and cathodic reactions were inhibited, and the corrosion rate was reduced by 1 order of magnitude. These results show that the biomineralized coating significantly improves the anti-corrosion performance of Q235 steel samples.

[0062] Comparative Example 2

[0063] The difference from Example 1 is that step (3) is not included, and only the culture time of step (2) is extended, so that the culture time of this comparative example is consistent with that of Example 1.

[0064] The obtained material has only biofilm on its surface, but no calcium carbonate deposition, so it has no anti-corrosion effect, indicating that Shewanella putrefaciens alone cannot achieve anti-corrosion effect.

[0065] Comparative Example 3

[0066] The difference from Example 1 is that calcium lactate is added in step (3) to replace calcium L-aspartate.

[0067] Figure 8 , Fig. 9 The macroscopic morphology and SEM images of the Q235 steel sheet with and without the biomineralization coating mediated by calcium lactate are shown respectively. Figure 1 As shown in the figure, compared with the control group, the surface of the Q235 steel sheet in the biomineralization coating group was covered with a gray-black product layer of about 25 μm, and no obvious corrosion signs were found. Fig. 9As shown, SEM observation revealed that a large number of rhombohedral mineralized particles were accumulated on the surface of the sample. Although the mineralized particles maintained the original triangular and rhombic shapes, the edges of the particles were relatively rounded, and by further magnification, small cylindrical particles could be found between the rhombohedral particles. Under the regulation of calcium lactate as a calcium source, Shewanella putrefaciens could induce the formation of a rough and thick biomineralized coating on the surface of the Q235 steel sheet sample.

[0068] Fig.10 The EDS composition analysis results of the biomineralized coating are shown. Fig.10 As shown in the figure, after testing its composition, it was found that the main components of its surface products are C, O, Ca and Mg. This shows that under the regulation of calcium lactate as a calcium source, Shewanella putrefaciens can induce the generation of CaCO on the surface of Q235 steel sheet samples. 3 Sedimentary layer.

[0069] Fig.11 The cross-sectional morphology observation and EDS component analysis results of the biomineralized coating are shown. Fig.11 As shown in the figure, the biomineralization coating mediated by calcium lactate has a large fluctuation, with the difference between the maximum and minimum thickness reaching about 15 μm, and no enrichment of Cl element occurs at the coating interface.

[0070] Figure 5 The XRD results of biomineralized coatings mediated by calcium lactate are shown. Figure 5 As shown in the figure, in the control group, signal peaks were detected at 44.7˚, 65.1˚, and 82.4˚ on the surface of the Q235 steel sample. Combined with the SEM morphology and EDS composition results, since the corrosion product layer on the surface of the Q235 steel sample in the control group was thin, only the characteristic peak of elemental iron was detected by XRD. In the biomineralization coating group, the diffraction peaks mediated by calcium lactate showed that the mineralization layer on the surface of the Q235 steel sample was composed of CaCO 3 , and the diffraction peak positions are 29.5˚, 37˚ and 47.9˚ respectively.

[0071] Fig.12 , Fig.13 The anti-corrosion performance test results of Q235 steel sheets with biomineralized coating mediated by calcium lactate are shown. Fig.12 (a, b) are the electrochemical impedance and Bode diagrams of Q235 steel samples in the control group. Fig.12(c, d) are the electrochemical impedance and Bode diagrams of the Q235 steel sample in the biomineralization coating group mediated by calcium lactate. The low-frequency impedance modulus of the Q235 steel sample in the biomineralization coating group mediated by calcium lactate continued to increase linearly with time, and finally reached the maximum value after immersion for 14 days. Its low-frequency impedance modulus increased by nearly an order of magnitude compared with the control group. Fig.13 The potentiodynamic polarization curves of Q235 carbon steel samples in the control group and the biomineralization coating group mediated by calcium lactate are shown in Figure 2. Compared with the control group, the polarization curve of the Q235 carbon steel sample mediated by calcium lactate also showed an obvious overall left shift, and both the anodic and cathodic reactions were inhibited, but the corrosion rate of the Q235 carbon steel sample was still higher than that mediated by calcium L-aspartate. These results show that the biomineralization coating mediated by calcium lactate can improve the anti-corrosion performance of Q235 steel samples, but the improvement effect is lower than that under the condition of calcium L-aspartate.

[0072] Comparative Example 4

[0073] The difference from Example 1 is that calcium nitrate is added in step (3) instead of calcium L-aspartate.

[0074] Fig.14 , Fig.15 The macroscopic morphology and SEM images of the Q235 steel sheet with and without the biomineralization coating mediated by calcium nitrate are shown respectively. Fig.14 As shown in the figure, compared with the control group, a large number of yellow-brown corrosion products appeared on the surface of the Q235 steel sheet in the biomineralization coating group, and more serious corrosion occurred. Fig.15 As shown, SEM observation revealed that there were a large number of pores on the surface of the loose rust layer, and rod-shaped bacteria could be observed mixed in the corrosion products between the pores. Under the regulation of calcium nitrate as a calcium source, Shewanella putrefaciens could form a large number of loose rust layers on the surface of the Q235 steel sheet sample.

[0075] Fig.16 The EDS composition analysis results of the biomineralized coating are shown. Fig.16 As shown in the figure, after testing its composition, it was found that the main constituent elements of its surface products are Ca and Cl elements. This shows that under the regulation of calcium nitrate as a calcium source, Shewanella putrefaciens can induce the formation of a rust layer with a loose structure on the surface of the Q235 steel sheet sample, which can enrich a large amount of inorganic salts.

[0076] Fig.17 The cross-sectional morphology observation and EDS component analysis results of the biomineralized coating are shown. Fig.18As shown in the figure, the biomineralized granular minerals mediated by calcium nitrate are interspersed in the rust layer and are discontinuous with each other, and are not tightly bonded to the carbon steel matrix. In addition, a large amount of Cl elements are found distributed in the rust layer and enriched at the interface.

[0077] Figure 5 The XRD results of biomineralized coating mediated by calcium nitrate are shown. Figure 5 As shown in the figure, in the control group, signal peaks were detected at 44.7˚, 65.1˚, and 82.4˚ on the surface of the Q235 steel sample. Combined with the SEM morphology and EDS composition results, since the corrosion product layer on the surface of the Q235 steel sample in the control group was thin, only the characteristic peak of elemental iron was detected by XRD. In the biomineralization coating group, only FeOOH and CaCO were detected under calcium nitrate-mediated regulation. 3 As well as the weak diffraction peak of Fe, it shows that the crystallinity of corrosion products on the sample surface is poor.

[0078] Fig.18 , Fig.19 The anti-corrosion performance test results of Q235 steel sheets with biomineralized coating mediated by calcium nitrate are shown. Fig.18 (a, b) are the electrochemical impedance and Bode diagrams of Q235 steel samples in the control group. Fig.18 (c, d) are the electrochemical impedance and Bode diagrams of the Q235 steel sample in the biomineralization coating group mediated by calcium nitrate. The capacitive arc radius in the low-frequency region of the Q235 steel sample in the biomineralization coating group mediated by calcium nitrate shows a continuous increasing trend over time. In the corresponding Bode diagram, obvious peaks appeared in the high-frequency region and the low-frequency region, respectively, indicating that a protective film layer appeared on the surface of the sample and the charge transfer process at the solid-liquid interface was suppressed, thereby alleviating the corrosion of the Q235 carbon steel sample. Fig.19 The potentiodynamic polarization curves of Q235 carbon steel samples in the control group and the biomineralization coating group mediated by calcium nitrate are shown in Figure 2. Compared with the control group, the polarization curve of the Q235 carbon steel sample mediated by calcium nitrate also showed an obvious overall left shift, and both the anodic and cathodic reactions were inhibited. However, when calcium nitrate was used as a calcium source, its corrosion current density increased significantly, indicating that the addition of calcium nitrate was not conducive to the corrosion inhibition of Shewanella putrefaciens on Q235 carbon steel.

[0079] Similarly, the use of calcium chloride cannot achieve the same effect as calcium L-aspartate.

[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for preparing a marine microbial mineralized coating, characterized in that: include: After the target metal material is aseptically treated, it is immersed in a culture solution of Shewanella putrefaciens for a first culture to obtain the metal material with a biofilm; adding calcium L-aspartate to the culture solution of the Shewanella putrefaciens to obtain a biomineralization nucleation solution, and performing a second culture to obtain a metal material with the marine microbial mineralization coating; The preparation method of the putrefactive Shewanella culture solution comprises: inoculating Shewanella putrefaciens into a marine liquid culture medium for a third culture to obtain the Shewanella putrefaciens culture solution; The marine liquid culture medium comprises: Peptone 4.9-5.1 g / L, Yeast extract powder 0.9-1.1 g / L, Ferric citrate 0.09-0.11 g / L, NaCl 19.35-19.55 g / L, MgCl2 5.95-6.01 g / L, Na2SO4 3.2-3.28 g / L, KCl 0.52-0.58 g / L, Na2CO3 0.13-0.19 g / L, KBr 0.05-0.11 g / L, SrCl2 0.031-0.037 g / L, SrBr2 0.05-0.11 g / L, H3BO3 0.019-0.025 g / L, NaSiO3 0.003-0.005 g / L, NaF 0.0021-0.0027 g / L, NH4NO30.0013-0.0019 g / L, NaH2PO4 0.005-0.011 g / L.

2. The method for preparing the marine microbial mineralized coating according to claim 1, characterized in that: The third culture is carried out at a temperature of 30-33°C, a stirring speed of 180-220 rpm, and a time of 14-18 hours; The ratio of the inoculation volume of the putrefactive Shewanella to the volume of the marine liquid culture medium is 1-2:100, and the concentration of the putrefactive Shewanella before inoculation is 1×10 7 -1×10 8 CFU / mL.

3. The method for preparing the marine microbial mineralized coating according to claim 1, characterized in that: The first culture temperature is 30-33°C and the time is 14-18h; The temperature of the second culture is 30-33° C., the time is 1-14 days, and the second culture is static culture.

4. The method for preparing the marine microbial mineralized coating according to claim 1, characterized in that: The concentration of calcium L-aspartate in the biomineralization nucleation solution is 2.74-2.8 g / L.

5. The method for preparing the marine microbial mineralized coating according to any one of claims 1 to 4, characterized in that: The calcium L-aspartate is sterilized before use and then filtered at room temperature using a 0.22 μm sterile microporous filter membrane.

6. A marine microbial mineralized coating, characterized in that: The method for preparing the marine microbial mineralized coating according to any one of claims 1 to 5 is used to prepare the coating.

7. The marine microbial mineralized coating according to claim 6, characterized in that: The marine microbial mineralized coating has an undulation degree of 3-3.4 μm.

8. The marine microbial mineralized coating according to claim 6 or 7, characterized in that: The thickness of the marine microbial mineralized coating is 12-15 μm.

Citation Information

Patent Citations

  • Method for simulating biological self-repairing of marine anticorrosive coating and application of shewanella putrefaciens

    CN115558380A

  • Self-repairing coating based on microbial mineralization, preparation method and use method of self-repairing coating and method for simulating seawater repair by using self-repairing coating

    CN116656215A